2010
DOI: 10.1017/s147266961000037x
|View full text |Cite
|
Sign up to set email alerts
|

Building Proficiency: Approaches to Teaching Legal Research at the College of Law

Abstract: Tony Simmonds describes the initiatives taken at the College of Law to assist students to perform effective practical legal research including a Legal Method foundation course; a vocational course for the Legal Practice Course and additional in house learning activities devised by the information professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The majority of the literature available comes from law librarians working within the academic sector; this isn't particularly surprising, given that the overwhelming majority of journal articles of all disciplines, are generated by those working in universities. There are a range of papers which present different approaches to teaching legal research (Donaldson, 2010; Eaton, 2010; Pope, 2009; Sales, 2013; Simmonds, 2010; Wakefield, 2007; Wieland, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the literature available comes from law librarians working within the academic sector; this isn't particularly surprising, given that the overwhelming majority of journal articles of all disciplines, are generated by those working in universities. There are a range of papers which present different approaches to teaching legal research (Donaldson, 2010; Eaton, 2010; Pope, 2009; Sales, 2013; Simmonds, 2010; Wakefield, 2007; Wieland, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the literature available comes from law librarians working within the academic sector; this isn't particularly surprising, given that the overwhelming majority of journal articles of all disciplines, are generated by those working in universities. There are a range of papers which present different approaches to teaching legal research (Donaldson, 2010;Eaton, 2010;Pope, 2009;Sales, 2013;Simmonds, 2010;Wakefield, 2007;Wieland, 2010). Sales (2013), found that it was necessary to overhaul the delivery of legal research training at the University of Salford due to two problems, firstly, that the timetabling of the sessions in lecture rooms resulted in a passive audience experience; and secondly, that during practical sessions, students were following demonstrations of how to search "on automatic pilot", and were neither retaining the knowledge, nor transferring it to their own research.…”
Section: University Programmesmentioning
confidence: 99%